Ascorbic acid iontophoresis for chondral gain in rats with arthritis - Arruda, Mauricio Ferraz de; Cassettari, Lucas Langoni [UNESP]; Neves, Lais Mara Siqueira das; Oliveira, Olga Maria Mascarenhas de Faria [UNESP]; Marcolino, Alexandre Márcio (Sociedade Brasileira de Ortopedia e Traumatologia, 2014)
OBJECTIVES: To examine the cellularity and thickness of the articular cartilage of the femur in rats with arthritis after treatment with iontophoresis. METHODS: To evaluate these objectives, a histological analysis was performed on hematoxylin and eosin, where cellularity and cartilage thickness were observed and evaluated qualitatively and quantitatively by manual counting by 700.09µm² area. RESULTS: The group treated with IAA had normal cellularity (40.1 cells/μm2) and maintenance of non-calcified cartilage (75.5μm), suggesting normal thickness. The non-treated group C+, on the other hand, had a lower mean number of chondrocytes (13.0μm2) (P <0.05) and, when the cartilage thickness was compared, it showed higher average thickness of calcified cartilage (104.8 mm) and lower mean of non-calcified cartilage (53.3μm) CONCLUSION: The use of iontophoresis with L-ascorbic acid by continuous electric current contributed to a quantitative gain of chondrocytes and improved the thickness distribution of calcified and non-calcified cartilage. Level of Evidence III, Case Control Study.
Keywords: Iontophoresis; Cartilage; Ascorbic acid